Bioproduction of Benzylamine from Renewable Feedstocks via a Nine‐Step Artificial Enzyme Cascade and Engineered Metabolic Pathways. Issue 13 (29th May 2018) - Zhou, Yi; Wu, Shuke; Mao, Jiwei; Li, Zhi
Abstract: Production of chemicals from renewable feedstocks has been an important task for sustainable chemical industry. Although microbial fermentation has been widely employed to produce many biochemicals, it is still very challenging to access non‐natural chemicals. Two methods (biotransformation and fermentation) have been developed for the first bio‐derived synthesis of benzylamine, a commodity non‐natural amine with broad applications. Firstly, a nine‐step artificial enzyme cascade was designed by biocatalytic retrosynthetic analysis and engineered in recombinant E. coli LZ243. Biotransformation of l ‐phenylalanine (60 mm ) with the E. coli cells produced benzylamine (42 mm ) in 70 % conversion. Importantly, the cascade biotransformation was scaled up to 100 mL and benzylamine was successfully isolated in 57 % yield. Secondly, an artificial biosynthesis pathway to benzylamine from glucose was developed by combining the nine‐step cascade with an enhanced l ‐phenylalanine synthesis pathway in cells. Fermentation with E. coli LZ249 gave benzylamine in 4.3 mm concentration from glucose. In addition, one‐pot syntheses of several useful benzylamines from the easily available styrenes were achieved, representing a new type of alkene transformation by formal oxidative cleavage and reductive amination. Abstract : Sustainable benzylamine : A novel nine‐step enzyme cascade was retrosynthetically designed and constructed for the first bio‐derived production of non‐natural benzylamine from biobased l ‐phenylalanine. The enzyme cascade was further integrated with the cellular metabolic pathway to achieve fermentative production of benzylamine from glucose.